ADVANTAGES AND CONTROVERSY OF COMMON AGRICULTURAL AND COHESION POLICY IN THE EU - Kostić, Vladimir; Simonović, Zoran; Kostić, Aleksandar (Economics of Agriculture, 2016)
The authors explore deals and payments that have a positive effect on the development of Common agricultural and cohesion policy. They particularly emphasize the ways of protecting the European Union from cheap imported products from non-EU countries. They also deal with the mechanisms that are built into the process, with the structural policy regarding "Agenda 2000", as well as the reforms of Common agricultural and cohesion policy from its beginnings until now. The paper presents problems of guaranteed prices, ecology, quotas, agricultural levies and customs duties. The authors also investigated the Common Agricultural and Rural Policy of the European Union 2014-2020, the ways to accelerate the transfer of technology and strengthen the cooperation between agriculture and research sectors in the future.